Operating conditions analysis of memristor model - Khadar Basha, N; T Ramashri, Dr (International Journal of Engineering and Technology, 2018)
The two terminal, fourth basic circuit element, memristor acts as nonlinear resistor with built-in memory functionality. Memristor has many advantages like non-volatile, no leakage current, Even when the power supply turn off, it retains its memory and typically apparent only at small scale. It shows significant effect in digital circuit application because it stores logic values without power consumption and logic values are measured based on the memristance value. Memristor is a class of non-volatile memory storage and is suitable for nanoscale memory applications. It is considered one of the most promising technology to implement memory and logic operations in a single cell. In this technology stored information is calculated as a low resistive state (LRS) and high resistive state (HRS). A detailed operating conditions of tunneling modulation model of memristor is studied and analyzed the operating frequency and voltage ranges in this paper. Switching behavior is measured based on the transition time of memristance change from one state to another state at different working frequencies.Â Â